Sustainability Analysis and Determination Cultivation Agribusiness Strategy of Soka Crab (Scylla Spp.) In Aceh Singkil Regency - Niswatin Hasanah; Ngani Alwirya Musi; Nanang Dwi Wahyono; Rizal Rizal (Journal of Development Research, 2023)
Soka crab or soft crab ( Scylla spp .) is becoming a seafood product that is increasingly popular among the public because it makes it easier for consumers to process and consume it. Soka crab has a high selling value compared to hard crab so that it becomes a prospect in pond business activities in the agribusiness of soka crab cultivation. Soka crab cultivation is generally carried out in coastal areas and natural resources are abundant and easily accessible. This research was conducted in the Crab King Gostel Jaya Crab King Gostel Jaya soft-crab aquaculture in Aceh Singkil Regency. , and future business actors in cultivating soka crabs in Aceh Singkil Regency. The analytical method used in this study is to use Multidimensional Scaling and Rapid Appraisal for Sustainability (MDS-RAPS) or Rapfis analysis to analyze the status of sustainability and Analytic Hierarchy Process (AHP) as an analytical tool in determining the strategy of soka crab ( Scylla spp. ) cultivation. The results of the analysis show that the first position on the sustainability status is the ecological dimension with environmental quality attributes. This study recommends the importance of the main strategy on the attributes of environmental quality for soft-crab cultivation as an effort for cultivators to develop agribusiness in the field of soft-crab cultivation.